MODERN APPROACHES TO THE PROBLEM OF CHRONIC ALCOHOLISM - Rustam Baxtiyarovich, Alkarov; Anvar Uzokboyevich, Turgunboyev (PT. Antis International Publisher, 2025)
Objective: The aim of this study is to investigate the long-term effects of ethanol intoxication on various body organs and systems, particularly focusing on the progression from minimal vascular damage to multi-organ pathology, as well as the development of specific clinical and psychopathological symptoms associated with alcoholism. Methods: This research employs a comprehensive review and analysis of existing studies on alcohol disease, examining its impact on microcirculation, organ morphology, and functional alterations caused by repeated ethanol exposure. Additionally, clinical data on the psychopathological symptoms exhibited by individuals with alcohol-related diseases are analyzed. Results: The findings highlight that chronic ethanol intoxication leads to significant morphological and functional changes in body organs, particularly affecting the vascular system and microcirculation. Over time, these alterations progress into multi-organ pathology, with clinical manifestations that include various psychopathological symptoms. Novelty: This study provides new insights into the specific mechanisms by which long-term ethanol exposure induces multi-organ pathology and psychopathological disorders. It emphasizes the gradual progression of alcohol disease, contributing to a deeper understanding of its pathophysiology and potential clinical interventions.